PERSAINGAN BISNIS RITEL: TRADISIONAL VS MODERN - Tri Joko Utomo (STIE Pelita Nusantara Semarang, 2011)
Competition between traditional and modern retail retail most invites attention, because it always puts the traditional retail in a weak position. Characteristics are inversely proportional to the difference weakens the position of traditional retail. Unclear regulations on the retail industry, especially regarding the distance of retail locations, adding a heavy effort to protect traditional retail.The scope of retail competition includes traditional and modern retail factors both internal and external factors, which include all the attributes in the performance aspects, aspects of consumer preferences and regulatory aspects. Aspects of consumer preferences include human resource (related to the services provided), merchandise, price and location.Strategy traditional retail competition with modern retail can be done through the application of model win–win development strategy, which is of mutual benefit or synergy.